Occurrence of Grease Lubricated Impact-Sliding Composite Wear - Zhendong Lv; Yiming Han; Rui Zhang; Jing Wang (Lubricants, 2022)
In industrial chain drives, the sleeve slides on the pin and impact loading occurs due to the polygon effect, while the collision between the ball and cage usually produces an impact-sliding motion in the rolling element bearings. Aiming at addressing the occurrence of surface damage caused by the impact-sliding motion, a ball–disk test rig employing optical interference technology was designed and built to realize load variation. Two kinds of commercial grease types, Klüber Centoplex 3 and Centoplex 2EP, were used in the experiments when the glass disk slides at a constant speed while the steel ball collides into them. The sliding and impact motions were controlled by PLC programming. After the experiments, the mid-section grease film distributions were measured using DIIM software. The results show that surface damage can rapidly occur even in the first working cycle, and that the phenomenon is affected by the sliding speed, maximum load, and grease consistency. When the sliding speed is low, multiple contacts of asperity peaks occur in the interior contact region and develop into adhesive wear. When the sliding speed increases, surface wear starts to occur at the side-lobe position of the elastohydrodynamic lubrication (EHL) horseshoe shape and extends with time accompanied by obvious surface scratches. The wear mechanism investigated provides valuable visible information for the further exploration of impact-sliding composite wear. It is suggested that great attention should be paid to impact-sliding wear occurring with grease lubrication since such working conditions are very common in industrial applications.